A capillary electrophoresis method for the determination of selected biogenic amines and amino acids in mammalian decomposition fluid - Swann, Lisa; Forbes, S.; Lewis, Simon (Elsevier, 2010)
A simple capillary zone electrophoresis method for the determination of selected biogenic amines (tyramine and tryptamine) and amino acids (tryptophan, phenylalanine and tyrosine) in mammalian decomposition fluids is presented. Separations were carried out in a fused silica capillary (75μA i.d.,total length 65 cm, effective length 56 cm) with detection by ultraviolet absorbance spectrophotometry at 200 nm. In order to improve resolution and total analysis time, the method was subjected to optimisation utilising a chemometric approach. A screening design was carried out followed by a central composite design (CCD), using peak resolution and total analysis time as response factors. The influences of four experimental variables (pH, background electrolyte concentration, percentage of organic modifier(methanol) and applied voltage) were investigated. Optimum separation conditions were determined to be; a background electrolyte of boric acid (70mM) adjusted to pH 9.5 with 0.1 M sodium hydroxide with 32% methanol (v/v). Applied voltage was 30 kV, with the resulting current being less than 26μA. Under these conditions the analytes were separated within 12 min. Tryptamine, tyramine, tryptophan, tyrosine and phenylalanine were identified by migration time and spiking in porcine decomposition fluids.